SAKRAL GEOGRAFIYANING О‘ZIGA XOS XUSUSIYATLARI - Safarov, I.B. (SCIENCE and SOCIETY, 2024)
This article describes the concept of sacral geography and its definitions of foreign scientists for the term “sacral geography”, the development of sacral geography as an independent field in the system of Geographic Sciences, the study and preservation of sacral legacies one of the tasks of sacral geography – proposals and recommendations for the development of internal pilgrimage and cognitive tourism.
Keywords: sacral; sacred; ancient; seed; tribe; space; mysterious places